Effectiveness and cost‐effectiveness of interventions that cause weight loss and reduce the risk of cardiovascular disease. Issue 1 (20th October 2016) - Zomer, Ella; Leach, Rachel; Trimmer, Christine; Lobstein, Tim; Morris, Stephen; James, William P.; Finer, Nick
Abstract : Background: Overweight/obesity is associated with significant morbidity, mortality and costs. Weight loss has been shown to reverse some of these effects, reducing the risk of chronic diseases such as cardiovascular disease (CVD). Aim: To determine the potential monies available, from an English National Health Service perspective, for weight loss interventions to be cost‐effective in the prevention of CVD. Methods: A Markov model was developed, populated with overweight/obese individuals from the Health Survey for England, aged 30–74 years, free of pre‐existing CVD and with available risk factor information to calculate CVD risk. All individuals were free of CVD at baseline and, with each annual cycle, could transition to other health states of primary CVD, secondary CVD or death according to transition probabilities for a maximum period of 10 years, or until death. Utilities, costs and the effects of weight loss on CVD risk factors were applied. The potential monies available for CVD prevention strategies, provided the incremental cost‐effectiveness ratio met UK arbitrary limits of between £20 000 and £30 000, was determined. Results: Applying the effects of weight loss on CVD risk factors prevented 4 CVD events and saved 17 quality‐adjusted life‐years over 10 years per 1000 individuals. £34 to £51 was available per person per year for up to 10 years when meeting the UK arbitrary limits. Conclusions: Individual annual financial allowances for weight loss interventions to be considered cost‐effective is relatively low; however, as a large proportion of the population is affected, wide cheap societal interventions are important.